Fungal Biomarkers Stability in Mars Regolith Analogues after Simulated Space and Mars-Like Conditions - Cassaro, Allessia; Pacelli, Claudia; Baqué, Mickael; de Vera, Jean Pierre Paul; Böttger, Ute; Botta, Lorenzo; Saladino, Raffaele; Rabbow, Elke; Onofri, Silvano (Journal of Fungi, 2021)
The discovery of life on other planets and moons in our solar system is one of the most important challenges of this era. The second ExoMars mission will look for traces of extant or extinct life on Mars. The instruments on board the rover will be able to reach samples with eventual biomarkers until 2 m of depth under the planet’s surface. This exploration capacity offers the best chance to detect biomarkers which would be mainly preserved compared to samples on the surface which are directly exposed to harmful environmental conditions. Starting with the studies of the endolithic meristematic black fungus Cryomyces antarcticus, which has proved its high resistance under extreme conditions, we analyzed the stability and the resistance of fungal biomarkers after exposure to simulated space and Mars-like conditions, with Raman and Gas Chromatography–Mass Spectrometry, two of the scientific payload instruments on board the rover.